Antibiotic adjuvants from Buxus sempervirens to promote effective treatment of drug-resistant Staphylococcus aureus biofilms. Issue 97 (5th October 2016) - Abreu, A. C.; Paulet, D.; Coqueiro, A.; Malheiro, J.; Borges, A.; Saavedra, M. J.; Choi, Y. H.; Simões, M.
Abstract : Plants have been long scrutinized in the quest for new antibiotics, but no strong antibiotic molecule was ever found. Abstract : Plants have been long scrutinized in the quest for new antibiotics, but no strong antibiotic molecule was ever found. Evidence exists that most phytochemicals have a regulatory or adjuvant effect on other antibacterial compounds, thus promoting a greater therapeutic effect. The current study assessed twenty-eight plants from different families for their antibacterial activity and as adjuvants in antibiotic therapy against Staphylococcus aureus, including methicillin-resistant S. aureus (MRSA). Eucalyptus globulus, Castanea sativa, Agrimonia eupatoria and Fraxinus excelsior methanolic extracts showed antibacterial activity with minimal inhibitory concentrations (MICs) of 0.125–0.5, 0.5–1.0, 1.0–2.0, and 2.0–4.0 g L −1, respectively. Non-antibacterial plants were assessed in combination with ampicillin, oxacillin, ciprofloxacin, erythromycin and tetracycline by a modified disc diffusion test. Methanolic extracts of Acacia dealbata, Prunus spp. plants, Centaurea nigra, Eupatorium cannabium and Buxus sempervirens showed a potentiating effect mostly of ciprofloxacin, erythromycin and tetracycline. B. sempervirens was selected for its potentiating activity and applied against S. aureus biofilms. B. sempervirens (1 g L −1 ) was able to cause an 88% reduction of S. aureus within 1 h exposure. Further phytochemical investigation of B. sempervirens allowed to identify betulinic acid as a major component, together with other triterpenoids. Betulinic acid and other common terpernoids – lupeol, betulin, hederagenin, ursolic acid and oleanolic acid, were tested for antibacterial and antibiotic-potentiating activities. Among the tested compounds, oleanolic acid and ursolic acid – were highlighted, showing MIC of 62.5 and 15.6 mg L −1, respectively, against S. aureus . Additionally, oleanolic acid showed synergism when combined with tetracycline and erythromycin and caused biofilm reductions of 70, 81 and 85% when applied at 1/2 MIC, MIC and 2 × MIC, respectively.